PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN MEDIA GOOGLE EARTH UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR KEWIRAUSAHAAN SISWA KELAS XI MULTIMEDIA SMK NEGERI 1 PAKEM: SMK NEGERI 1 PAKEM - ABDUL ASIS (Mitra Pendidikan, 2022)
This research was conducted with the aim of knowing the increase in interest and learning outcomes of entrepreneurship through the application of discovery learning learning models with google earth media for students of Class XI Multimedia at SMK Negeri 1 Pakem. The type of research used in this research is Classroom Action Research (CAR). Classroom action research can be defined as an action research carried out by the teacher as well as a researcher in the classroom or together with other people (collaboration) by designing, implementing and reflecting collaborative and participatory actions that aim to improve or improve the quality of the learning process in the classroom. class through a certain action in a cycle (Kunandar.2010). This research is collaborative, namely between the implementer of the action (teacher) and the party who observes the process of the course of action (observer). The subjects in this study were students of class XI Multimedia at SMK Negeri 1 Pakem in the odd semester of the 2020/2021 school year, totaling 27 students. The implementation of school action research is carried out at SMK Negeri 1 Pakem which is located at Jalan Raya Pakem, Patemon Village, Pakem District. Bondowoso Regency for 3 months, from September to November 2020. Data collection techniques used in this research are 1). Observation, 2) Documentation and 3) Test. The data analysis technique used in this study was carried out by 1). Data analysis by comparing the number of active questioning students before treatment with cycle I, and cycle II 2). Comparing the number of student assignments on time before the treatment was carried out with cycle I, and cycle II 3). Comparing the number of student assignments on LKPD and quizzes above the KKM before treatment with cycle I, and cycle II. Based on the above, the results of research and discussion based on classroom action research carried out by applying the Google Earth Discovery Learning Media learning model to increase the interest and learning outcomes of class XI Multimedia SMK Negeri 1 Pakem students, the authors can conclude as follows: 1) Interest, student learning interest after treatment with Discovery Learning learning increased as evidenced by the increased intensity of asking and answering as well as timeliness in collecting assignments 2) Learning Outcomes, Learning outcomes obtained after treatment at the time of observation increased from before getting treatment, this is indicated by the increasing number of students receiving the value of the assignment is above KKM